PERBANDINGAN LUARAN MODEL GLOBAL ATMOSFER CCAM dan GFS di wilayah INDONESIA DAN SEKITARNYA - Donaldi Sukma Permana (Widyariset, 2010)
The aim of this research was to compare Conformal Cubic Atmospheric Model (CCAM) and Global Forecast System (GFS) prediction against GFS initial condition as control up to 7 days in the future over Indonesia and northern subtropical regions of Indonesia in September – October – November (SON) 2008. Comparison was conducted in spatially to observe the similarity pattern by calculating spatial correlation value for some basic parameters in several pressure vertical levels. The result described that output of both models showed general similarity pattern in SON 2008 over Indonesia and northern subtropical regions of Indonesia, obtained spatial correlation values indicated GFS prediction was slightly better compared by CCAM prediction. For some parameters, CCAM output showed a particular problem in low-pressure vertical level (250mb). There was probably a problem with the vertical interpolation of the GFS initial data onto the CCAM conformal-cubic grid.